The auctioning of urban highway franchises - Serra, Pablo (Estudios de Economía, 2016)
Urban highways are a scarce resource. For this reason, the auction of urban highway franchises to the private sector should take into account the congestion which affects them. In this paper a form of auction is proposed which consists of fixing maximum tolls, taking social welfare into account at both peak hours and off-peak hours, and then, following the proposal of Engel, Fischer and Galetovic, by granting the franchise to the applicant that demands the least revenue for constructing and operating the highway until such revenue has been collected. The authority could temporarily raise either or both maximum tolls.